Effect of increasing the foot area on the load-velocity relationship of the underwater dolphin kick - Wang, S.; Zhao, Y.; Chen, X.; Shen, Y. (Journal of Human Kinetics, 2025)
The objective of this study was to evaluate the impact of augmenting the foot area (by wearing fins) on the load-velocity relationship of the underwater dolphin kick (UDK) and to investigate the optimal loading zone of resistance training for the UDK. Seventeen swimmers underwent a semi-tethered swimming test and a 15-m maximum swim velocity test, both with and without fins (FINS and WF, respectively). The study revealed that the UDK's load-velocity relationship, when using semi-tethered swimming, displayed a robust linear correlation (R2 = 0.88 ± 0.15). The FINS condition enhanced the optimization of the load-velocity relationship, resulting in a substantial rightward shift (R2, AIC, BIC optimized by 15%-65%) and elevating the UDK velocity by 10%-22% across seven load levels. The effective load level rose from 57 N to 69 N (R = 0.70-0.85, p < 0.05); however, the FINS condition altered the original UDK technique, leading to a 7% decrease in the stroke rate (SR) and a 19% increase in stroke length (SL). Consequently, wearing fins modified the load-velocity relationship of the UDK and augmented the power output level. We recommend that athletes use semi-traction swimming to improve UDK performance with a maximum load of no more than 57 N or a velocity of no less than 73% of maximum velocity; wearing fins allows this range to be extended to 69 N and 71% of maximum velocity.